2020
DOI: 10.1101/2020.10.27.356972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parabrachial complex processes dura inputs through a direct trigeminal ganglion-to-parabrachial connection

Abstract: Migraines cause significant disability and contribute heavily to healthcare costs. Irritation of the meninges outermost layer (the dura mater), and trigeminal ganglion activation contribute to migraine initiation. Maladaptive changes in central pain-processing regions are also important in maintaining pain. The parabrachial complex (PB) is a central region that mediates chronic pain. PB receives diverse sensory information, including a direct input from the trigeminal ganglion. We hypothesized that PB processe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…101 While most input to the PBN is likely mediated by SpN neurons, a recent study demonstrated a direct dural afferent projection to the PBN. 102 The PAG is involved in ascending and descending pain modulation and affective responses to pain. It receives ascending input from Vc neurons and descending inputs from subcortical regions including the hypothalamus.…”
Section: Brainstem and Diencephalic Mechanisms Of Headache Brainstem ...mentioning
confidence: 99%
See 1 more Smart Citation
“…101 While most input to the PBN is likely mediated by SpN neurons, a recent study demonstrated a direct dural afferent projection to the PBN. 102 The PAG is involved in ascending and descending pain modulation and affective responses to pain. It receives ascending input from Vc neurons and descending inputs from subcortical regions including the hypothalamus.…”
Section: Brainstem and Diencephalic Mechanisms Of Headache Brainstem ...mentioning
confidence: 99%
“…101 While most input to the PBN is likely mediated by SpN neurons, a recent study demonstrated a direct dural afferent projection to the PBN. 102…”
Section: Brainstem and Diencephalic Mechanisms Of Headachementioning
confidence: 99%